A multa diária como meio de coerção para a efetivação da tutela jurisdicional que impõe às partes obrigação de fazer, não fazer ou entregar coisa certa - Cruz, Marcos Vinício Raiser da (2010)
The aim of this essay is to study the applicability of the daily fine stated by article 461 of the Brazilian Civil Procedure Code astreintes that can be imposed to a defendant, to assure the obedience of a court ruling regarding an obligation to do something, to not do something, or to give something to someone. We do not have the ambition of completely cover the subject. The subject calls attention because in several occasions, most of the parties, benefited by a daily fine, deviate from the main goal of the lawsuit to pursue only the astreintes, because its value, timely increased, became so disproportional in comparison to the value of the matter in discussion, that such matter is no longer appealing. The astreintes, considering its indubitable comminatory nature, shall comply the debtor to fulfill, rapidly and willingly, the obligation imposed by the court ruling and it has to have a daily value defined with no understatement or exaggeration. Despite the fact that the experts agree upon the non existence of a maximum value, considering the law principles of proportionality and equitableness, it is important that the fine fixed by the Judge be compatible with the case and remains suitable with the obligation to be demanded from the debtor. The reason of the fine is not, and never was, to grant a unjust enrichment to anyone, considering that it benefits, mostly, the plaintiff. We will show, in the conclusion, that the astreintes, having a judicial nature and a specific goal, shall not be used as a way or an instrument to punish the unwilling debtor, once the Brazilian Civil Procedure Code, to such purpose, already has a more suitable alternative, which is the fine for contempt of court, that besides having its value defined by law (20% of the case value), what does not apply to the astreintes as above mentioned, has a different beneficiary, because the amount would be paid to the State